Occupational Exposure to Environmental Tobacco Smoke: A Study in Lisbon Restaurants - Pacheco, Solange (2012)
Environmental tobacco smoke (ETS), also referred to as secondhand smoke (SHS), is a major threat to public health and is increasingly recognized as an occupational hazard to workers in the hospitality industry. Therefore, several countries have implemented smoke-free regulations at hospitality industry sites. In Portugal, since 2008, legislation partially banned smoking in restaurants and bars but until now no data have been made available on levels of indoor ETS pollution/exposure at these locations. The aim of this study was to examine the occupational exposure to ETS/SHS in several restaurants in Lisbon, measured by indoor fine particles (PM2.5) and urinary cotinine concentration in workers, after the partial smoking ban in Portugal. Results showed that the PM2.5 median level in smoking designated areas was 253 μg/m3, eightfold higher than levels recorded in canteens or outdoor. The nonsmoking rooms of mixed restaurants exhibited PM2.5 median level of 88 μg/m3, which is higher than all smoke-free locations studied, approximately threefold greater than those found in canteens. Importantly, urinary cotinine concentrations were significantly higher in nonsmoker employees working in those smoking designated areas, confirming exposure to ETS. The proportion of smokers in those rooms was found to be significantly positively correlated with nonsmoker urinary cotinine and indoor PM2.5 levels, establishing that both markers were occupational-ETS derived. The use of reinforced ventilation systems seemed not to be sufficient to decrease the observed ETS pollution/exposure in those smoking locations. Taken together, these findings demonstrate that the partial restrictions on smoking in Portuguese venues failed to provide adequate protection to their employees, irrespective of protective measures used. Therefore, a smoke-free legislation protecting individuals from exposure to ETS/SHS in all public places and workplaces is urgently needed in Portugal.